2009
DOI: 10.1080/10408390802067936
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Applications in Vegetables and Fruits: A Review

Abstract: There is an increasing trend both in advanced countries and many developing countries to centrally process fresh fruits and vegetables, properly packaged, for distribution and marketing. Irradiation technology proved to be effective in reducing post-harvest losses, and controlling the stored product insects and the microorganisms. Gamma irradiation was employed to restrain potato sprouting and kill pests in grain. Irradiation proved to be extremely beneficial in terms of prolonging the fruit and vegetable shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
6

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 82 publications
6
75
0
6
Order By: Relevance
“…However, Bari et al (2005) reported that the appearance, color, texture, taste, and overall acceptability of broccoli and mung bean sprouts, irradiated at 1.0 kGy, did not undergo significant changes after seven days of post-irradiation storage at 4°C, in comparison with control samples. Arvanitoyannis et al (2009) reviewed the impact of irradiation dose on the shelf life and microflora and sensory and physical properties of fish, shellfish, molluscs, and crustaceans; and observed that the shelf life prolongation of fish products was even 3-5 times longer than the traditionally employed methods. Bai et al (2004) studied that the shelf life of ethanol and heat pretreated slices were 15 to 16 and 12 days, which was 7 and 3 to 4 days longer than that of non-pretreated controls (8 to 9 days), respectively, based on the visual observance.…”
Section: Overall Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bari et al (2005) reported that the appearance, color, texture, taste, and overall acceptability of broccoli and mung bean sprouts, irradiated at 1.0 kGy, did not undergo significant changes after seven days of post-irradiation storage at 4°C, in comparison with control samples. Arvanitoyannis et al (2009) reviewed the impact of irradiation dose on the shelf life and microflora and sensory and physical properties of fish, shellfish, molluscs, and crustaceans; and observed that the shelf life prolongation of fish products was even 3-5 times longer than the traditionally employed methods. Bai et al (2004) studied that the shelf life of ethanol and heat pretreated slices were 15 to 16 and 12 days, which was 7 and 3 to 4 days longer than that of non-pretreated controls (8 to 9 days), respectively, based on the visual observance.…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…Kharel and Hasinaga (1996) reported that high electric field exposure for short period suppresses the respiration rate and extended the freshness of strawberries. Arvanitoyannis et al (2009) reviewed that the irradiation treatment was extremely beneficial in terms of prolonging the fruit and vegetable shelf life by 3-5 times. Pre-exposure to short UV radiation slowed down respiration and ripening of fruits stored at room temperature, thus enhancing their shelf life (Baka et al 1999;Siddiqui et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation beneficial effects include reduction of storage losses, shelf life extension, and improvement of microbiological and parasitological safety of foods, while being safe to the environment. Hence, irradiation might be considered a promising conservation technology, bearing in mind that the doses applied on fresh fruits and processed fruit products are limited by the impact on their quality (Arvanitoyannis et al, 2009). Particularly, gamma-irradiation was already applied to diverse food products such as tuber and bulb crops, stored grains, dried ingredients, meats, poultry and fish, or fruits (Farkas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But, less than 1.5 log10 reductions should be expected for the most radiation sensitive fruits. In many cases, surface decontamination of fruits, pre-washed and packaged vegetables and ready-to-eat fresh processed products with chemical agents should be less efficient (by at most 2 log10 reduction) than food irradiation (Arvanitoyannis et al, 2009). Most studies indicated that, the irradiation of fresh fruits led to a reduction in firmness.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Applicable doses on fruit products are limited by their impact on quality (Arvanitoyannis et al, 2009). Irradiation should anticipate 2 to more than 5 log10 reduction of pathogenic (non spore forming bacteria), in some fresh and many processed fruits.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%